Hubungan Kecerdasan Emosional dan Kemampuan Penyesuaian Diri Mahasiswa Perantau - Julia, Rosandra Rizky; Putri, Rani Mega (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Self-adjustment is an important factor for migrant students in facing social and academic challenges. Emotional intelligence is considered one of the factors that support self-adjustment. This study aims to determine the relationship between emotional intelligence and self-adjustment among overseas students in the Guidance and Counseling Department  at Sriwijaya University. This study used a quantitative approach with a correlational design. The population of the study consisted of 149 overseas students, with a sample size of 109 students. The instruments used were the emotional intelligence scale and the self-adjustment scale, both of which have been tested for validity and reliability. Data analysis was conducted using the Pearson Product Moment correlation technique. The results showed a positive and significant relationship between emotional intelligence and self-adjustment among overseas students, with a correlation coefficient of 0.745 and a significance value of 0.000 (p < 0.05). This means that the higher the emotional intelligence of students, the better their ability to adjust. Emotional intelligence contributes 55.5% to the self-adjustment ability of migrants. This finding highlights the importance of emotional intelligence in helping overseas students adapt to their social and academic environments.